-2(1-4x)=6x+12

Simple and best practice solution for -2(1-4x)=6x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(1-4x)=6x+12 equation:


Simplifying
-2(1 + -4x) = 6x + 12
(1 * -2 + -4x * -2) = 6x + 12
(-2 + 8x) = 6x + 12

Reorder the terms:
-2 + 8x = 12 + 6x

Solving
-2 + 8x = 12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-2 + 8x + -6x = 12 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-2 + 2x = 12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-2 + 2x = 12 + 0
-2 + 2x = 12

Add '2' to each side of the equation.
-2 + 2 + 2x = 12 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = 12 + 2
2x = 12 + 2

Combine like terms: 12 + 2 = 14
2x = 14

Divide each side by '2'.
x = 7

Simplifying
x = 7

See similar equations:

| 7(7x-1)-18=47x+7 | | 8b=2b | | 64c^2-16=0 | | 5(2x-4)=0 | | -8(x+3)+2x+5=7x+9 | | 3+x+27=180 | | (2x+3)(4x-4)= | | [9(p+4)-18]-[2(p-4)+1]= | | 9(2k+3)+2=11(k-.5) | | .4x+7=.6x | | 2c-7=18 | | .8x-.2y-.1x-1.2y=.7 | | y-3/3-y-2/2=-1 | | 18/65=x/35 | | 9(q+9)= | | 13(4x+4)=3(5x+6) | | 5x=23+y | | 100(29)=10(29) | | 2xsquared-x=3 | | Y/9-6=-14 | | 5x+9=9+2x | | 8x-11/7=-5 | | z/15-6=14 | | 3x-12=-4x+32 | | v=(p*q)-((p*q)/100*5)-p | | -2=6/8 | | 3(16-4y)4y=8 | | 8-9s+s^2= | | 1015=2x+5 | | 4-3d=8 | | -9x-6=-3(3x+2) | | d=2m+3m |

Equations solver categories